Drug Utilization 90% in Patients with Acute Hemorrhagic Stroke to Assess Adherence to Standard Anti-Hypertensive Treatment - Girase GD (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The early management of hypertension in hemorrhagic stroke affects the extent of brain injury and patient suffering’s. This study conducted at civil hospital Nashik, describes antihypertensive treatment in acute hemorrhagic stroke do not adhere to standard treatment, DU 90% not achieved. As in first 30 patients no patients were prescribed with recommended drugs, interim analysis was performed on 16% of sample size. Antihypertensive drugs were prescribed as single drug or in combination, Cap Nifedepin (40%) was most frequently prescribed single drug.. Calcium Channel Blockers were preferred with or without combination with beta-blocker agent; Mean cost per patient treated was 2280?.